2017
DOI: 10.1002/ejlt.201700283
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals and Antioxidant Activity Degradation Kinetics During Long‐Term Storage of Rapeseed Oil Pressed From Microwave‐Treated Seeds

Abstract: The present study focuses on the kinetics of degradation of phytochemicals and antioxidant capacity during long‐term storage of rapeseed oils prepared from microwave (MV) pre‐treated seeds (2–10 min, 800 W). A maximum tocochromanols (90.48 mg/100 g) and phenolic compounds (mainly canolol, 1692.15 μg g−1) concentration is achieved after 10 min of seeds MV pre‐treatment, while the highest content of carotenoids (1017.51 μg/100 g) is found in the oils pressed from seeds exposed to microwaves for 6 min. During sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Canolol exhibited an increase of up to 317% by effect of the microwave pretreatment, indicating the production of this compound with microwave radiation, and of up to 2564% in the H‐EthF phases with respect to the oils obtained by P2, presenting a larger concentration thereof (Table ). These results show that an antioxidant‐rich byproduct was obtained, containing 83% of the canolol of the OF obtained by P1.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Canolol exhibited an increase of up to 317% by effect of the microwave pretreatment, indicating the production of this compound with microwave radiation, and of up to 2564% in the H‐EthF phases with respect to the oils obtained by P2, presenting a larger concentration thereof (Table ). These results show that an antioxidant‐rich byproduct was obtained, containing 83% of the canolol of the OF obtained by P1.…”
Section: Resultsmentioning
confidence: 96%
“…Canolol accounts for 85% of total phenolics in crude canola oil . Several authors studied the effect of microwave pretreatment on oilseed extraction and the tocopherol content of canola oil extracted with hexane, and by cold‐pressing reported an increase in the canolol concentration of canola oils due to a microwave pretreatment. In previous works, a content of 27 mg kg −1 of canolol was reported for canola oil extracted with hexane, and of 168 mg kg −1 for canola oil extracted with hexane from microwave‐pretreated seeds, while a content of up to 532 mg kg −1 was observed in canola oil extracted by pressing from seeds subjected to combined hydrothermal‐microwave pretreatments .…”
Section: Introductionmentioning
confidence: 99%
“…Rapeseed oil has lower oxidative stability as compared to olive oil [6,7]. Several studies have been performed to assess quality degradation of rapeseed oil during photo-and autooxidation and storage [8][9][10][11][12][13][14]. It was found that the overall quality during storage was influenced by the type of container material (plastics, glass), storage conditions (light, temperature, oxygen availability), and time [13].…”
Section: Introductionmentioning
confidence: 99%